Lactic Acid Accumulation During Exhaustive Exercise Impairs Release of Neutrophil Extracellular Traps in Mice - Shi, Yue; Shi, Hui; Nieman, David C.; Hu, Qiongyi; Yang, Luyu; Liu, Tingting; Zhu, Xiaofeng; Wei, Hongzhan; Wu, Die; Li, Fei; Cui, Yanqiu; Chen, Peijie (Frontiers in Physiology, 2019)
Lactic acid (LA) is a sensitive indicator of exercise intensity and duration. A single bout of prolonged and intensive exercise can cause transient immuno-suppression through the interaction of cellular, humoral and hormone factors. Exercise-induced influences on neutrophil extracellular traps (NETs) release have been reported, but the underlying mechanism is unknown. This study investigated NETs release, cell-free DNA (cf-DNA), and LA concentration in mice after 60 and 145 minutes of intensive, graded treadmill running. The concentration of LA and cf-DNA increased while the level of myeloperoxidase-DNA (MPO-DNA) (an indicator of NETs release) decreased during 145 minutes of exhaustive running. LA was positively and negatively correlated with cf-DNA and MPO-DNA (R2=0.57 and 0.53, respectively, both p<0.001). Subsequent in vitro experiments were conducted with neutrophils activated by phorbol myristate acetate (PMA) in the presence of LA at different concentrations. Increasing LA concentrations were associated with decreases in NETs release and reactive oxygen species (ROS) formation. Taken together, this work furthers our understanding of how NETs and oxidative reaction respond to one bout of prolonged and intensive running. The data support a negative relationship between LA accumulation and NETs release after heavy exertion.